A philosophy of nationhood and the modern self - Rozynek, Michal (Palgrave Macmillan, 2020)
This book delves into the philosophical presuppositions of modern political agency. Michal Rozynek explores the place of nationalism in an increasingly cosmopolitan world by approaching the fundamental questions of modern subjectivity from a new angle. Taking as a starting point the transformations of the modern self, this volume argues that the project of modernity leads to an unresolvable tension within the self-- one which seemingly jeopardizes our ability to participate in a public world.